2019
DOI: 10.1021/acs.macromol.8b02013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hydration and Sulfonation on the Morphology and Ionic Conductivity of Sulfonated Poly(phenylene) Proton Exchange Membranes

Abstract: Multiple computational and experimental techniques are used to understand the nanoscale morphology and water/proton transport properties in a series of sulfonated Diels–Alder poly­(phenylene) (SDAPP) membranes over a wide range of temperature, hydration, and sulfonation conditions. New synthetic methods allow us to sulfonate the SDAPP membranes to much higher ion exchange capacity levels than has been previously possible. Nanoscale phase separation between the hydrophobic polymer backbone and the hydrophilic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(102 citation statements)
references
References 102 publications
4
96
0
Order By: Relevance
“…58 Identification of these mechanisms has been shown in previous works to be crucial to fully understanding trends in ionic conductivity. 59,60…”
Section: Resultsmentioning
confidence: 99%
“…58 Identification of these mechanisms has been shown in previous works to be crucial to fully understanding trends in ionic conductivity. 59,60…”
Section: Resultsmentioning
confidence: 99%
“…Pulsed-Field-Gradient (PFG) NMR Analysis: 1 H pulsed field gradient (PFG) NMR experiments were performed on a Bruker AVANCE III 600 instrument using a DIFF50 (40 A, maximum strength of 1800 G cm −1 ) z-gradient 5 mm water-cooled diffusion NMR probe at 1 H observed frequency of 600.13 MHz. The bipolar stimulated echo pulse sequence was used, with the translational self-diffusion coefficients (DT) evaluated from the variation in signal intensity with gradient strength I g using the Stejkal and Tanner relation [38] as implemented in the TOPSPIN…”
Section: Methodsmentioning
confidence: 99%
“…b) Comparison of proton conductivity data for IPC‐COF membrane (solid stars), COF materials (open diamonds) [ 26–29,31 ] and state‐of‐the‐art PEMs (open triangles). [ 2,9,10,37–39 ] c) Proton conductivity of IPC‐COF membrane and Nafion 212 versus RH at 40 °C.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…53,59 Previous research on similar materials has found that proton conductivity at high degrees of acid functionalization and high hydration number, such as the materials discussed in this work, stems from a combination of the Grotthuss (structural diffusion) and vehicular mechanisms of proton transport. 60 The relationship between proton conductivity and proton mobility is highlighted in Eqn (4), 53,59 where ⊞ H+ is the proton conductivity, F is Faraday's constant, [SO 3 H] is the analytical acid concentration www.soci.org N Peressin, M Adamski, S Holdcroft wileyonlinelibrary.com/journal/pi within a swollen membrane (as per Eqn (5)), and ⊘ 0 H+ is the effective proton mobility. The consequence of this relationship is somewhat contradictory: an increase in water sorption (water content) within a membrane may result in increased proton conductivity due to the presence of more bulk-like water, and yet decreased analytical acid concentration, which in turn lowers effective proton mobility and proton conductivity.…”
Section: Mechanical Propertiesmentioning
confidence: 99%